PENGARUH TINGKAT PENDIDIKAN DAN PERSEPSI TERHADAP PARTISIPASI MASYARAKAT DALAM PENGELOLAAN DAYA TARIK WISATA AIR TERJUN SELENDANG ARUM, SONGGON - BANYUWANGI - Prananda Putra, Adetiya (Jurnal Master Pariwisata (JUMPA), 2018)
The development of tourism sector by involving the community will result in a success that suitable with the aspirations and needs of the community itself. The aim of this research is to identify the level of community participation, the affect of the level of education and the perception on community participation in managing Selendang Arum Waterfall as a tourist attraction. This research uses survey method. The samples of this research are 136 people of Sumber Arum Villager. The result of this research shows that level of Sumberarum villager participation in managing Selendang Arum Waterfall is 83%, it implies highly positive (active community participation). Based on the results of the analysis, the perception has a significant affect on community participation, however the level of education does not have a significant affect on community participation and simultaneously the level of education and the perception have a significant affect on the community participation.